What is the need and why is it time for innovative models for understanding lung repair and regeneration? - Weiss, Daniel J. (Frontiers in Pharmacology, 2023)
Advances in tissue engineering continue at a rapid pace and have provided novel methodologies and insights into normal cell and tissue homeostasis, disease pathogenesis, and new potential therapeutic strategies. The evolution of new techniques has particularly invigorated the field and span a range from novel organ and organoid technologies to increasingly sophisticated imaging modalities. This is particularly relevant for the field of lung biology and diseases as many lung diseases, including chronic obstructive pulmonary disease (COPD) and idiopathic fibrosis (IPF), among others, remain incurable with significant morbidity and mortality. Advances in lung regenerative medicine and engineering also offer new potential avenues for critical illnesses such as the acute respiratory distress syndrome (ARDS) which also continue to have significant morbidity and mortality. In this review, an overview of lung regenerative medicine with focus on current status of both structural and functional repair will be presented. This will serve as a platform for surveying innovative models and techniques for study, highlighting the need and timeliness for these approaches.